2003
DOI: 10.1161/01.cir.0000087402.13786.d0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the Radial Artery Used for Myocardial Revascularization

Abstract: Background-No information is available on the long-term results of radial artery (RA) grafts used as coronary artery bypass conduits. Methods and Results-In this report, we describe the long-term (105Ϯ9 months) angiographic results of a series of 90 consecutive patients in whom the RA was used as a coronary artery bypass conduit directly anastomosed to the ascending aorta. The long-term patency and perfect patency rates of the RA were 91.6% and 88%, respectively, versus 97.5% and 96.3% for internal thoracic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(51 citation statements)
references
References 15 publications
0
48
0
3
Order By: Relevance
“…As with a RIMA graft, the radial artery may be used as a free or composite graft with the goal of providing greater arterial revascularization ( Figure 10.27). Patency rates are similar but perhaps slightly superior to GSV grafts [55].…”
Section: Radial Arterymentioning
confidence: 83%
See 1 more Smart Citation
“…As with a RIMA graft, the radial artery may be used as a free or composite graft with the goal of providing greater arterial revascularization ( Figure 10.27). Patency rates are similar but perhaps slightly superior to GSV grafts [55].…”
Section: Radial Arterymentioning
confidence: 83%
“…Utilization of free radial artery graft as a CABG conduit is dependent on surgeon preference or lack of availability of a suitable vein conduit [55]. Initial attempts at using radial artery grafts were complicated by frequent graft closure.…”
Section: Radial Arterymentioning
confidence: 99%
“…In contrast, other studies have shown excellent early-, mid-, and long-term patency of the RA. 4-7 A 10-year patency rate of 91.8% was reported in an observational study, 8 and RA patency was found to be higher than that for SVG after 1 year in a large, randomized comparative study. 9 Hence, the RA has become the arterial conduit following internal thoracic arteries (ITAs), 10 and here we provide further evidence that it shows excellent early-and mid-term patency.…”
Section: Discussionmentioning
confidence: 95%
“…Possati, et al reported the long-term (105 ± 9 months) graft patency of RA grafts in a series of 90 consecutive CABG patients [36].…”
Section: The Radial Artery (Ra)mentioning
confidence: 99%